Effect of seed priming on improvement of germination of Vicia villosa under allelopathic components of Eucalyptus camaldulensis - Saberi , Morteza; Tarnian , Farajollah (Plant Breeding and Seed Science, 2012)
The objective of this study was to evaluate the effectiveness of seed priming in improving seed germination and seedling vigor of Vicia villosa under laboratory conditions. Chemical stimulators included: gibberellic acid (125,250 and 500 ppm), salicylic acid (100,200 and 300 mg/lit) and extract of Eucalyptus camaldulensis (0, 25, 50, 75 and 100 %). This experiment was carried out as factorial experiment based on a randomized completely design, with four replications. The results showed that Eucalyptus camaldulensis extract had inhibitive effect on germination and early seedling growth of Vicia villosa. Early seedling growth of Vicia villosa increased by pretreatment of seeds in chemical stimulators so that the highest effect was observed in gibberellic acid (250 ppm). The chemical stimulators don’t have any effect on germination speed. Interaction effects of allelopathic and pretreatment with chemical stimulators were significance on germination percentage, root, shoot and plant length and seed vigor index.